Food - Delivery Start-Ups : In Search of the Core - Bajaj, Karuna; Mehendale, Smita (Prabandhan: Indian Journal of Management, 2016)
In the era of growth of Internet-based start-ups, the food technology business is fast emerging as a service to watch out for. Double-digit growth and spectacular predictions for the future despite cut throat competition have led to considerable excitement in this space. Food technology start-ups attracted considerable investor interest in 2015. However, in the first quarter of 2016, funding slowed down, taking a toll on cash starved food startups. Last year witnessed either closure or scaling down of operations of few pioneering start-ups in the food delivery business in various cities in India. This has compelled the food tech startups to revisit strategies and take a relook at their business models. Rather than burning cash in the name of customer acquisition, its time these companies start creating value for restaurants and customers alike. On this premise, the secondary research was undertaken for the period up to March 2016 to examine the key success factors and viability of the food-delivery business.